Legal Formulation of Imposing Administrative Sanction for Anti-Covid-19 Vaccinations Movement - Rusdianto Rusdianto; Diva Pitaloka (Universitas Negeri Semarang, 2022)
In order to accelerate the handling Covid-19, the Government has issued a policy that impose administrative sanction for those refusing Covid-19 vaccination. This journal underlines and focuses the administrative sanction for those who refuse to take the vaccinations. Those sanctions could be social security termination, and/or administrative service moratorium. While it is assumed that this policy is urgently needed in addressing the pandemic issue, it also leads to other issues. The first is that whether those administrative sanctions are compliant with law principles and human rights protection. Another is whether there are legal implications for those who refuse to take vaccinations. Method adopted in this research is normative law research method based on facts, issues, regulations, analysis, and conclusion (FIRAK). This journal points out two results. Firstly, the right to obtain health service is a part of human rights. In order to fulfill that right and to achieve a greater good, the Government is responsible to create a clean and healthy environment. Thus, providing Covid-19 vaccinations and imposing administrative sanction comply with law principles and human rights protection. The latter, legal implication from such policy is that the vaccination is mandatory. Thus, those refusing it would be imposed administrative sanctions. It is expected that this policy would become a legal formulation in addressing and handling the Covid-19 pandemic.